Pengaruh Arus Kas Operasi Dan Laba Bersih Terhadap Return Saham Tahun 2016-2019 - Anggun Sundari; Dian Hakip Nurdiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study has the aim of sizzling, analyzing and analyzing the operating flow and net income on stock returns in 2016-2019 in the agricultural sector. This study uses secondary data contained in the Indonesia Stock Exchange. With the sample technique carried out by the author, the authors obtained a sample of this study as many as 8 companies from 21 companies in the agricultural sector, from 2016-2019 with annual data from operating flows and net income to stock returns, resulting in 32 data in this study. The results showed that partially Operating Cash Flow has no effect on Stock Returns and Net Profit does not have a partial effect on Stock Returns, while the results of simultaneous research on Operating Cash Flow and Net Profit have no effect on Stock Returns. Keywords: Operating Cash Flow, Net Income, Stock Return